Innovative MOF-enhanced electroanalytical approach for sensitive sunitinib malate detection in renal carcinoma patients using CuO/lanthanum MOF-modified carbon paste electrode - Azza H. Rageh; Mohamed I. Said; Asmaa Abdeltawab; Fatma A.M. Abdel-aal (Talanta Open)
This study uniquely emphasizes the crucial role of MOF synthesis techniques in optimizing electrocatalytic properties and enhancing electroanalytical performance. The main aim of this work is to develop a highly sensitive, selective, and cost-effective electrochemical sensor for detecting sunitinib malate (SUN) in serum samples collected from renal cancer patients. The designed sensor was based on using CuO nanoparticles/lanthanum 1,4-napthalene dicarboxylic acid (NDC) MOF-modified carbon paste electrode (CuO NPs/LaNDC-MOF/CPE) coupled with square-wave adsorptive anodic stripping voltammetry (SW-AdASV) as the electrochemical technique. Two MOF synthetic approaches were utilized i.e. conventional (Conv.) and solvothermal (Solvo.). The synthesized La-MOFs were characterized using X-ray Diffraction analysis (XRD), Fourier transform IR spectroscopy (FTIR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and Nitrogen adsorption/desorption isotherm (BET). LaNDC-MOF (Conv.) has a higher surface area (four times) than LaNDC-MOF (Solvo.). Moreover, the modified electrode based on LaNDC-MOF (Conv.) exhibited better electrocatalytic activity and improved sensitivity towards the oxidation of SUN than that prepared through solvothermal route. Various experimental parameters, including accumulation potential, accumulation time, and pH of the supporting electrolyte, were optimized to obtain the best analytical performance. The fabricated sensor based on CuO NPs/LaNDC-MOF/CPE showed an oxidation peak of SUN at 0.66 V vs Ag/AgCl. Under the optimized conditions, SW-AdASV method exhibited a linear response over a concentration range of 0.01–1.0 μmol l-1 with a detection limit of 0.002 μmol l-1 for SUN. The proposed method was successfully applied for the determination of SUN in pharmaceutical formulations and serum samples of renal cancer patients. Moreover, the proposed methodology via modification of CPE with the synthesized MOFs tailors them to be applied for clinical analysis and therapeutic drug monitoring of SUN, providing a valuable tool for personalized medicine and improving the treatment outcomes for renal cancer patients.